Altered B cell compartment associated with Tfh cells in children with Henoch-Schonlein Purpura - Ning Zhang; Ge Tian; Yuanyuan Sun; Jing Pan; Wei Xu; Zhe Li (BMC, 2021)
Abstract Aim IgA-producing B cells have been found to be associated with children diagnosed with Henoch-Schonlein purpura (HSP). The aim of the present study was to determine whether children with HSP possess altered B-cell subsets. Methods A total of 14 children diagnosed with HSP and age- and sex-matched healthy controls (HCs) were enrolled in our study. Peripheral blood mononuclear cells were isolated, and the percentage and absolute number of B-cell subsets and Follicular helper T (Tfh) cells were determined by flow cytometry. Finally, Spearman's correlation coefficient was used to analyse the correlation between the percentage of Tfh cells and B-cell subsets. Results We found that compared to HCs, the frequency and absolute number of total B cells were significantly higher in children with HSP, but the percentages of plasma cells and naïve B cells were significantly lower. A significantly increased percentage and absolute number of memory nonswitched B cells were found in children with HSP compared with HCs. We observed that the expression of C-X-C chemokine receptor type 5 (CXCR5) on total CD4+ T cells and the percentage of CD4+CXCR5+ cells were significantly increased in patients with HSP. Moreover, significantly correlations between Tfh cells and various B-cell subsets were observed. Conclusions Our study showed a Tfh-cell-associated altered B cell compartment in children with HSP.